Blood Transfusion and Outcome After Transfemoral Transcatheter Aortic Valve Replacement - Maaranen P.; Husso A.; Tauriainen T.; Lahtinen A.; Valtola A.; Ahvenvaara T.; Virtanen M.; Laakso T.; Kinnunen E.-M.; Dahlbacka S.; Juvonen T.; Mäkikallio T.; et al. (W.B. Saunders, 2022)
Objective: To investigate the prognostic impact of red blood cell (RBC) transfusion on the outcome after transfemoral transcatheter aortic valve replacement (TAVR).
Design: Nationwide, retrospective multicenter study.
Setting: Five University Hospitals.
Participants: The nationwide FinnValve registry included data from 2,130 patients who underwent TAVR for aortic stenosis from 2008 to 2017. After excluding patients who underwent TAVR through nontransfemoral accesses, 1,818 patients were selected for this analysis.
Intervention: TAVR with or without coronary revascularization.
Measurements and Main Results: RBCs were transfused in 293 patients (16.1%). Time-trend analysis showed that the rates of RBC transfusion decreased significantly from 27.5% in 2012 to 10.0% in 2017 (p < 0.0001). Among 281 propensity score matched pairs, RBC transfusion was associated with higher 30-day mortality (7.1% v 0%, p < 0.0001), late mortality (at 5-year, 59.1% v 43.3%, p = 0.008), as well as increased risk of acute kidney injury (17.0% v 4.4%, p < 0.0001), renal replacement therapy (3.6% v 0.4, p < 0.0001) and prolonged hospital stay (mean, 8.5 v 4.7 days, p < 0.0001) compared with patients who did not receive blood transfusion. In the overall series, the risk of adverse events increased significantly with the increasing amount of transfused RBC units and when operation for excessive bleeding was necessary. Consistently with these findings, postoperative hemoglobin drop and nadir level were associated with higher early and late mortality.
Conclusions: Patients who received blood transfusion after TAVR had an increased risk of early and late adverse events. These adverse effects were particularly evident with increasing amount of RBC transfusion and operations for excessive bleeding.